Non-ideality and deep bound states in plasmas - Ebeling, Werner; Pöschel, Thorsten (Lectures on Quantum Statistics, 2019)
With increasing density of plasmas, non-ideality effects become more and more apparent. This is of particular importance for plasmas with deep bound states, that is, when the thermal energy is smaller than or of the same order as the ground state energies of the atoms in the plasma. For hydrogen this is the case already for T < 10 5 K. Then, except for very low density, the convergence of the expansions becomes worse and we have to consider higher order terms. Sometimes even the transition to other expansion parameters, as the fugacity is recommended.
CRIS-Team Scopus Importer:2019-05-28